Analysis of National Road Slope Risk Level Based on Geographic Information System - Menudi, La; Lakawa, Irwan; Sufrianto, Sufrianto; Ilham, Vickky Anggara (Sultra Civil Engineering Journal (SCiEJ), 2022)
The purpose of this study is to investigate the failure and instability of slopes, control and evaluate treatments and create slope data in a geographic information system as a planning data base to determine the level of risk, hazard consequences and the distribution of slopes along the National road in Konawe Selatan district. In this study using the Bina Marga slope survey method, which is to provide a score or value for each parameter measured in the field and a database is made using a geographic information system (GIS) to state the level of slope risk using the Bina Marga standard value. The results showed that the slopes spread on the Awunio – Lapuko and Lainea – Awunio National roads were dominated by artificial slopes, namely 4 embankment points and 5 excavation points and 1 natural slope point. From the results of the investigation and data collection on the slopes, the data is processed using the formula R = 0.9.H + C. where R is the risk level value, H is the hazard value and C is the consequence value. The conclusion from the above research results is that the slopes at the study site are dominated by artificial slopes with slope characteristics of soil, sand and weathered rock so that the slopes are unstable and have a high level of risk.